Geography - Barker, David; Broadbent, Chris; Harris, Helen (Hodder Education, 2021)
Help your students to develop the geographical skills and knowledge they need to succeed using this new Edition Student book, which includes new case studies and practice questions. Written by our expert author team, the new edition is structured to provide support for A-Level Geography learners of all abilities. The book includes: · Activities and regular review questions to reinforce geographical knowledge and build up core geographical skills · Clear explanations to help students to grapple with tricky geographical concepts and grasp links between topics · Case studies from around the world to vividly demonstrate geographical theory in action · Exciting fieldwork projects that meet the fieldwork and investigation requirements This student book is supported by digital resources on our new digital platform Boost, providing a seamless online and offline teaching experience.